The ascension of the soul towards Allah: a critical reading of Ibn Bajah's soul theory - Al-Salahi, Ayad Kareem (International Journal of Psychosocial Rehabilitation, 2020)
It is arguable that Ibn Bajah's self-study constitutes a theory which is a scientific hypothesis linking between coordinate introductions and perceptions. Ibn Bajah believes that self makes man one by number despite the variation in his symptoms and his conditions; self is the source of unity and motivation regardless of body changes .The existence of the self, for him, is one of the innate things that do not need evidence to prove. If we try to prove its existence it would have seemed more difficult than we think. As for the question of its fate and immortality, Ibn Bajah showed that the individual self-perishes with the annihilation of the body. The body is perishable, but mind is Immortal. Since the mind is holistic (according to Ibn Baja), then holistic immortality is for the mind. This principle is the cornerstone of his philosophy, which can sustain the movement upward towards The One. The immortality that people aspire to is nothing more than to remain in the memory of the people with the great works and vestigaes as stated by Gigamish Epic seven thousand years ago.